Aditions to the Flora of Colombia Aditions to the Flora of Colombia - Hermann J. F. (Caldasia)
During the first four months of 1944 while the writer was engaged in exploration for sources of rotenone in Colombia, principally in the Eastern Llanos, some opportunity was found for general botanical collecting. Although both time and facilities for this purpose were limited to the extent that somewhat less than 500 numbers were obtained, these collections included a few undescribed plants and several species apparently not so far reported from Colombia. In addition to the two novelties described in the present paper, new species in the genera Axonopus, Grimaldia, Piper, Calolisianthus (genus new to Colombia), Hyptis, Bartsia, Castilleja, Alloplectus and Cephaelis will be described elsewhere by specialists in those groups, and new records for Lonchocarpus have already been published (Journ. Wash. Acad. Sci. 37: 111-113. 1947). During the first four months of 1944 while the writer was engaged in exploration for sources of rotenone in Colombia, principally in the Eastern Llanos, some opportunity was found for general botanical collecting. Although both time and facilities for this purpose were limited to the extent that somewhat less than 500 numbers were obtained, these collections included a few undescribed plants and several species apparently not so far reported from Colombia. In addition to the two novelties described in the present paper, new species in the genera Axonopus, Grimaldia, Piper, Calolisianthus (genus new to Colombia), Hyptis, Bartsia, Castilleja, Alloplectus and Cephaelis will be described elsewhere by specialists in those groups, and new records for Lonchocarpus have already been published<span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> (Journ. Wash. Acad. Sci. 37: 111-113. 1947).